2019
DOI: 10.14202/vetworld.2019.671-676
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine from krill increases plasma choline and its metabolites in dogs

Abstract: Background and Aim: Choline and its metabolites have multiple physiological roles in the body, which are important for muscle function, memory, methylation reactions, and hepatic lipid transport. This study aimed to investigate, if inclusion of phosphatidylcholine (PC) from Antarctic krill (Euphausia superba) can increase the concentration of choline and its metabolites in plasma of sled dogs in comparison to a control group. Materials and Methods: Ten adult Alaskan Huskies of both genders were supplemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Choline chloride is commonly used to provide choline in balanced dog foods, but it is known to affect the activity of other elements of the premix due to its hygroscopic properties (Moghimi and Roosta 2019). Substitution of choline for phospatydilcholine in dogs (originating from a crustacean) indicated that it is feasible to use this source to maintain physiological levels of choline and its metabolites in plasma (Burri et al 2019). Studies in lactating rats fed with phospatydilcholine have confirmed the previous statement through phospatydilcholine measurements in the plasma of suckling pups and immune response, due to its contribution to splenocytes (Lewis et al 2016).…”
Section: Discussion Experiments 1 -Palatability Studymentioning
confidence: 99%
“…Choline chloride is commonly used to provide choline in balanced dog foods, but it is known to affect the activity of other elements of the premix due to its hygroscopic properties (Moghimi and Roosta 2019). Substitution of choline for phospatydilcholine in dogs (originating from a crustacean) indicated that it is feasible to use this source to maintain physiological levels of choline and its metabolites in plasma (Burri et al 2019). Studies in lactating rats fed with phospatydilcholine have confirmed the previous statement through phospatydilcholine measurements in the plasma of suckling pups and immune response, due to its contribution to splenocytes (Lewis et al 2016).…”
Section: Discussion Experiments 1 -Palatability Studymentioning
confidence: 99%
“…RBC and plasma were separated by centrifugation at 3000 rpm for 15 min at room temperature and kept on dry ice until stored at −80°C. The plasma was used for the analysis of choline and its metabolites and the results are described in a separate publication [ 24 ]. RBCs were analyzed as described previously at Omegametrix GmbH (Martinsried, Germany) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…A typical omega-3 source is fish oil, where the omega-3 PUFAs are bound to triglycerides (TGs), but more recently also products from krill have been included in diets for pets [ 7 , 8 ]. Krill meal is made from Antarctic krill ( Euphausia superba ) to provide a mix of proteins and fat, the latter being characterized by a high content of omega-3 PUFAs bound in PLs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fasting plasmatic TMAO level of lactating seals was 45 ± 20 µmol/L, while peak levels upon feeding ranged in a specific individual from 83 to 1040 µmol/L, (mean 324 ± 110 µmol/L). A report shows that dogs fed with krill (Euphausia superba) have a marked increase in choline levels and in plasmatic TMAO (krill 32.4 ± 12.6 vs. control 4.4 ± 4.7 µmol/L, six-week treatment) [82].…”
Section: Tmao In Animal Body Fluidsmentioning
confidence: 99%